Apparatus Behavior in Public Services in Yosonegoro Village, Limboto District, West Gorontalo Regency - Idji, Rusli Abdurrahman (Journal of Public Representative and Society Provision, 2023)
This study aims to determine Apparatus Behavior in Public Services in Yosonegoro Village, Limboto District, West Gorontalo Regency. This research is to use a descriptive research method with a qualitative approach. Based on the description above on the research on the behavior of officials that has been carried out in Yosonegoro Village, Limboto Barat District, Gorontalo Regency, it can be concluded as follows; (1) Concern in serving the community is maximized, responds quickly to what the community needs and provides HP numbers to the community so they can be easily contacted and serve quickly; (2) Discipline of officials in serving the community is maximized, with reference to Standard Operations (SOP) for working on time and completing work on time; (3) The responsibility of the apparatus in serving the community is optimal by carrying out the work on time, being responsible for the leadership and their duties and functions.